Parody of the “Sensitive Traveller” Type in the Russian Travelogues of the First Third of the 19th Century - Konstantinova, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article analyses Russian travelogues of the first third of the nineteenth century, which are variations of parodies of the “Karamzin canon”. The study focuses on the “sensitive traveller” as a type of the subject of narrative characteristic of the sentimental travel of the early nineteenth century. The author refers to both popular parody texts of travelogues (for example, My Journey, or the Adventures of One Day by N. P. Brusilov and A Sensitive Journey along Nevsky Prospekt by P. L. Yakovlev) and those unknown to the wider audience. The article presents an analysis of the anonymous text A Sensitive Journey to St Petersburg of a Village Nobleman, published in two issues of the journal Otechestvennye Zapiski for 1826 which has not been carried out before. The research aims to systematise the main approaches to the study of Russian parody travelogues of the first third of the nineteenth century, determine the functions of parody on the type of “sensitive traveller”, and identify the influence of parody texts on the evolution of the travelogue genre in the historical and literary process. As a result of the analysis, the author concludes that the appearance of parody travelogues was associated with the crisis of sentimentalism as a mode in the Russian historical and literary process of the nineteenth century; the main objects of parodies were the key elements of the “Karamzin canon”, “common places”, which demonstrated the inconsistency of the principles of sentimental poetics of travel. Parodies of the “sensitive traveller” type demonstrated the authors’ excessive fascination with the description of sensitivity and subjectivity of perception of the travel event, which led to a distortion of the main parameters of the narrative structure of the travelogue, a lack of fabula, and leveling of the status of the travel event. In this connection, parody travelogues began to depict “a journey without a journey”, “a journey before a journey”, “an imaginary journey”, etc. Thus, parodies of the travelogue genre and the type of “sensitive traveller” turned out to be a popular phenomenon in the Russian historical and literary process in the first third of the nineteenth century and demonstrated the need to transform the narrative structure of the travel text.